2013
DOI: 10.1371/journal.pone.0076532
|View full text |Cite
|
Sign up to set email alerts
|

Altered Colonic Mucosal Polyunsaturated Fatty Acid (PUFA) Derived Lipid Mediators in Ulcerative Colitis: New Insight into Relationship with Disease Activity and Pathophysiology

Abstract: ObjectivesUlcerative colitis (UC) is a relapsing inflammatory disorder of unconfirmed aetiology, variable severity and clinical course, characterised by progressive histological inflammation and with elevation of eicosanoids which have a known pathophysiological role in inflammation. Therapeutic interventions targetting eicosanoids (5-aminosalicylates (ASA)) are effective first line and adjunctive treatments in mild-moderate UC for achieving and sustaining clinical remission. However, the variable clinical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 54 publications
2
53
0
2
Order By: Relevance
“…A study demonstrated significant changes in the formation of LOX-derived 5-HETE, 12-HETE and 15-HETE with an association of higher levels and worse post-transplant graft function outcome in human kidney transplantation, indicating a critical role of lipid metabolites in the pathophysiology of post-transplantation organ dysfunction [18]. This is further supported by another study that found significantly elevated 5-HETE, 11-HETE, 12-HETE and 15-HETE levels in colonic mucosal biopsies from ulcerative colitis patients correlating with inflammation severity [19]. …”
Section: Introductionmentioning
confidence: 83%
“…A study demonstrated significant changes in the formation of LOX-derived 5-HETE, 12-HETE and 15-HETE with an association of higher levels and worse post-transplant graft function outcome in human kidney transplantation, indicating a critical role of lipid metabolites in the pathophysiology of post-transplantation organ dysfunction [18]. This is further supported by another study that found significantly elevated 5-HETE, 11-HETE, 12-HETE and 15-HETE levels in colonic mucosal biopsies from ulcerative colitis patients correlating with inflammation severity [19]. …”
Section: Introductionmentioning
confidence: 83%
“…Although there is evidence that exogenous PGE 2 administration can attenuate DSS-induced damage [49], the effects of PGD 2 treatment is unknown. We also examined levels of HETEs given that they have been shown to impact upon the inflammatory process [50] and 5-HETE in particular has been found to be elevated in mucosal biopsies from colitis patients[51]. Interestingly, 5-HETE was increased in the colons of mPGES-1 −/− mice following DSS administration, an effect not observed in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while the expression of the other CYP1 family members, CYP1A1 and CYP1A2, is generally down‐regulated by inflammation (Morgan, ), CYP1B1 expression is induced by inflammatory cytokines (Piscaglia et al, ; Bleau et al, ; UmannovĂĄ et al, ). Moreover, CYP1B1 also metabolizes endogenous compounds such as arachidonic acid to give hydroxyeicosatetraenoic acids (HETEs), which are involved in inflammation in general and inflammatory bowel diseases in particular (Masoodi et al, ). This oxidation of arachidonic acid by CYP1B1 is of biological significance as CYP1B1‐produced mid‐chain HETEs have been recently implicated in doxorubicin‐induced cardiotoxicity (Maayah et al, ).…”
Section: Introductionmentioning
confidence: 99%